Recovery of paralyzed limb motor function in canine with complete spinal cord injury following implantation of MSC-derived neural network tissue. (October 2018) - Wu, Guo-Hui; Shi, Hui-Juan; Che, Ming-Tian; Huang, Meng-Yao; Wei, Qing-Shuai; Feng, Bo; Ma, Yuan-Huan; Wang, Lai-Jian; Jiang, Bin; Wang, Ya-Qiong; Han, Inbo; Ling, Eng-Ang; et al.
Abstract: We have reported previously that bone marrow mesenchymal stem cell (MSC)-derived neural network scaffold not only survived in the injury/graft site of spinal cord but also served as a "neuronal relay" that was capable of improving the limb motor function in a complete spinal cord injury (SCI) rat model. It remained to be explored whether such a strategy was effective for repairing the large spinal cord tissue loss as well as restoring motor function in larger animals. We have therefore extended in this study to construct a canine MSC-derived neural network tissue in vitro with the aim to evaluate its efficacy in treating adult beagle dog subjected to a complete transection of the spinal cord. The results showed that after co-culturing with neurotropin-3 overexpressing Schwann cells in a gelatin sponge scaffold for 14 days, TrkC overexpressing MSCs differentiated into neuron-like cells. In the latter, some cells appeared to make contacts with each other through synapse-like structures with trans-synaptic electrical activities. Remarkably, the SCI canines receiving the transplantation of the MSC-derived neural network tissue demonstrated a gradual restoration of paralyzed limb motor function, along with improved electrophysiological presentation when compared with the control group. Magnetic resonance imaging and diffusion tensor imaging showed that the canines receiving the MSC-derived neural network tissue exhibited robust nerve tract regeneration in the injury/graft site. Histological analysis showed that some of the MSC-derived neuron-like cells had survived in the injury/graft site up to 6.5 months. Implantation of MSC-derived neural network tissue significantly improved the microenvironment of the injury/graft site. It is noteworthy that a variable number of them had integrated with the regenerating corticospinal tract nerve fibers and 5-HT nerve fibers through formation of synapse-like contacts. The results suggest that the transplanted MSC-derived neural network tissue may serve as a structural and functional "neuronal relay" to restore the paralyzed limb motor function in the canine with complete SCI.